SIMULACION DE FLUJO 1D EN CANALES ABIERTOS - Yzocupe, Víctor A. (2006)
It presents the formulation of a one-dimensional numerical model for simulation of flow in rivers and channels. The model is general and flexible; because it permits to simulate a broad range of flow conditions, such as uniform and non-uniform flow, steady and unsteady. The model does not consider problems of filtration, sediment transport, rainfall, evaporation, neither wind. The model is based in the numerical approximation of the governing equations of flow in open channels (Saint Venant’s equations) using the implicit finite difference Preissmann scheme. The computation variables are the discharge (Q) and the water surface level (Z). The algorithms applied in the segments of the reach under study plus the boundary conditions compose one system of lineal equations, which is solved using the Double Sweep method. It presents some schematic tests for a prismatic rectangular channel. There are some tests for steady uniform and non-uniform flow, also some tests for non-steady flow, which demonstrate the goodness of the model.